Pendampingan Wirausaha Muda Dalam Pengelolaan Keuangan di MTs Al-Istiqamah Desa Karangjaya Kabupaten Sukabumi: Pengabdian - Jimatul Arrobi; Yosa Sobariahah; Rika Oktaviani; Deden Muhammad Ismail; Adisti Nurfatimah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Young Entrepreneurs Financial Management Mentoring Program at MTs Al-Istiqamah was implemented to foster an entrepreneurial spirit while improving students' financial management skills. The background to this activity stems from common problems often experienced by young entrepreneurs, namely weak transaction recording, mixing capital and profits, and lack of discipline in managing cash flow. The method used was Participatory Action Research (PAR) based on community organizing, involving students as the main subjects, accompanied by supervising teachers and KKN students. The series of activities included interactive counseling, simple cash recording workshops, business simulations, school bazaar practices, and joint evaluations. The program results showed an increase in students' ability to create neat, transparent, and easy-to-understand financial reports. In addition to the technical impact, this activity also encouraged the formation of a school young entrepreneur community, fostering leadership, cooperation, and a new awareness towards social transformation within the MTs Al-Istiqamah environment.